2018
DOI: 10.2147/opth.s148990
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repeated Ozurdex injections on ocular hypertension

Abstract: PurposeThe purpose of this study was to correlate the degree of ocular hypertension with the number of Ozurdex injections.MethodsIntraocular pressure (IOP) fluctuations for a total of 183 injections were studied over a period of at least 12 months. The main indications for treatment were uveitis, diabetic macular edema, and retinal vein occlusion.ResultsResults of the study demonstrate that repeated Ozurdex injections do not increase the frequency of IOP spikes beyond 30 mmHg. For lower IOPs, however, a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In patients receiving multiple injections, some studies showed no correlation between the number of injections and the risk of developing ocular hypertension, 19 , 31 while one study found an increased risk for IOP spikes below 30 mmHg. 32 Our study showed a higher mean IOP after the second injection. This increase was low, but statistically significant (P <0.05).…”
Section: Discussionsupporting
confidence: 48%
“…In patients receiving multiple injections, some studies showed no correlation between the number of injections and the risk of developing ocular hypertension, 19 , 31 while one study found an increased risk for IOP spikes below 30 mmHg. 32 Our study showed a higher mean IOP after the second injection. This increase was low, but statistically significant (P <0.05).…”
Section: Discussionsupporting
confidence: 48%
“…Additionally, SAFODEX study revealed that repeated IVD resulted in more OHTN 21 . However, another study reported that multiple IVD did not increase the frequency of IOP spikes beyond 30 mmHg 31 . While a previous study reported high myopia to be a risk factor for OHTN after IVD implantation 21 , we found that a short axial length may represent an additional risk factor for OHTN.…”
Section: Discussionmentioning
confidence: 94%
“…The above referenced studies showed an average of 29% of patients will have an IOP > 25 mmHg or 10 mmHg above baseline. Recent data showed that following multiple injections of intravitreal dexamethasone, 53% had an IOP greater than or equal to 23 mmHg; 42% with IOP great than or equal to 25 mmHg; and 11% greater than or equal to 30 mmHg [12]. The SAFODEX study evaluated ocular hypertension secondary to intravitreal dexamethasone when used for all etiologies.…”
Section: Discussionmentioning
confidence: 99%